Productivity and Profitability of Basmati Rice Varieties under SRI - Panigrahi, Trinath; Garnayak, L. M.; Ghosh, M.; Bastia, D. K.; Ghosh, D. C. (International Journal of Bio-resource and Stress Management, 2023)
The results of a field experiment conducted during the kharif season of 2007 and 2008 at OUAT, Bhubaneswar on basmati rice varieties under system of rice intensification (SRI) showed that application of organic manure (FYM 15.0 t ha-1) improved growth attributes like plant height, tillering, LAI and CGR of basmati rice varieties, increased panicle production and filled grains panicle-1, produced high grain (4.42 t ha-1 ) and straw (6.57 t ha-1 ) yields and fetched the high gross return comparable to those of INM (50% RDF+7.5 t FYM ha-1), but significantly greater than those of inorganic fertilization (RDF). However, use of RDF (60-30-30 kg N-P2O5-K2O ha-1) was more remunerative in terms of net returns and returns per rupee invested than organic manuring or INM practice due to higher cost of organic manures. The basmati rice variety Pusa Basmati-1 performed better than Geetanjali. Similarly, crop planted at close spacing (20×20 cm2) showed improved growth and increased yield and profit over those of wide spacing (25×25 cm2); but growth, yield and economics of basmati rice did not vary much between the crops planted with 10 and 15-day old seedlings. The results suggest to grow Pusa Basmati-1 at 20×20 cm2 spacing with 10 or 15-day old single seedlings under organic manuring or INM practice for better growth, higher yield and greater profit.